Morphological Characterization of Horsegram Genotypes (Macrotyloma uniflorum L. Lam) - , Anisa M. Nimbal, Dharshan M (Archives of Current Research International, 2024)
Under the provisions of New Seed Policy and the Protection of Plant Varieties and Farmers Rights Act, 2001, all newly developed varieties have to be registered based on the criteria of Novelty, Distinctness, Uniformity and Stability (NDUS) information helps in easy identification of horsegram genotype for each other. In the present study breeder seeds of 24 horse gram genotypes were obtained from pulse breeder, Agricultural Research Station Bailhongal and Regional Agricultural Research Station, Vijayapur for conducting the field experiment at Saidapur Farm University of Agricultural Sciences, Dharwad. The present study was carried out to have information on morphological distinctness of 24 horse gram genotypes for plant height, number of branches, seed coat, flower colour, pod colour, number days taken for pod initiation and pod maturity. All the horsegram genotypes under study were distinguished based on the morphological traits such as days to fifty percent flowering, pod colour and seed coat colour. Among the them seed coat colour and pod colour were most important morphological characters in distinguishing horsegram genotypes as they were least affected by environmental factors. The genotypes differing for. morphological traits serve as markers for maintenance, multiplication and seed certification and also serve as diverse parent for further breeding programe.